Bahasa Inggris - Agnes Dwi Meita Sari; Lita Wahyu Rika Wati; Theresa Dwi Kurnia (Innofarm : Jurnal Inovasi Petanian, 2025)
Sorghum (Sorghum bicolor L.) is a cereal crop with strong potential as an alternative food source, animal feed, and bioenergy material due to its adaptability to marginal, dry, and nutrient-poor soils. In Indonesia, however, local sorghum utilization remains limited because of the lack of improved varieties and insufficient knowledge of growth and phenology. This study analyzed the growth phases and phenological traits of two East Sumba genotypes, Watar Hammu Miting Walla and Watar Hammu Rara Kadita. The research was conducted at the Experimental Farm of the Faculty of Agriculture, UKSW (June–December 2024), using morphological observations and growth-phase documentation until flowering. Variables measured included leaf traits, chlorophyll content, plant height, stem diameter, sugar content, seed weight and size, and panicle form. Both genotypes exhibited similar growth patterns, but Miting Walla progressed through early phases more rapidly. Morphologically, Miting Walla had narrower leaves, sturdier stems, higher sugar levels, and compact panicles, while Rara Kadita had wider leaves, taller stems, lighter seeds, and looser panicles. These contrasts indicate distinct adaptive strategies and underline the potential of local sorghum as a dual-purpose crop for food and bioenergy. Keywords: Growth stage, Phenology, Characteristics of sorghum, Food alternative